(untitled) (Praxis Educativa, 2012)
In the field of Social Sciences, and particularly in the field of education, it is not simple to approach research models or paradigms because there are frequent discussions raised around this topic in dichotomy terms, sometimes antagonistic. It is possible to meet different stances in relation to the generation of scientific knowledge, that is, in relation to the way of ´producing science,ª which implies thinking of models or paradigms that support the different research logics. The objective of this paper is to characterize the main research models or paradigms in education with the purpose of carrying out a methodological analysis of the Research Project: ´Professional Socialization Referents in Universidad Nacional de RÌo Cuarto teachersª (Argentina). In the first part a characterization of the models or paradigms is developed; in the second part, a synthesis of the mentioned Project is presented, and in the third part both an analysis and justification of the project is carried out.